A ratiometric fluorescent probe for detecting the endogenous biological signaling molecule superoxide anion and bioimaging during tumor treatment. Issue 5 (14th January 2020) - Wang, Yue; Wang, Xiaoyan; Zhang, Li; Huang, Yan; Bi, Liyan; Lv, Changjun; Chen, Lingxin
Abstract : A fluorescent probe for O2 ˙ − detection during tumor treatment revealed that curcumin can sensitize cisplatin for tumor treatment by inducing severe O2 ˙ − burst. Abstract : Tumor resistance and drug-induced nephrotoxicity pose great challenges to the clinical treatment of tumors, and they also limit the clinical application of oncology drugs. Finding an effective adjuvant, which can sensitize tumor treatment, is an effective method for tumor treatment. Here, we developed a ratiometric fluorescent probe, TP-Tfs, for superoxide anion (O2 ˙ − ) detection in living cells and in vivo during the process of tumor treatment for the first time. TP-Tfs with simple synthesis steps and high yields can detect O2 ˙ − sensitively and selectively, and the detection limit was determined to be 37 nM. Using TP-Tfs, we found that cis -diaminodichloroplatinum(ii ) (DDP) was effective in treating tumors by inducing O2 ˙ − burst. Curcumin (cum) can sensitize tumor treatment effectively by inducing more severe O2 ˙ − burst. These results indicated that the probe TP-Tfs was a promising candidate for drug screening and tumor treatment evaluation.